Patient profi le of a tertiary obstetric-cardiac clinic - van der Merwe, J.L.; Hall, D.R.; Herbst, P.; Doubell, A. (SA Heart Journal, 2017)
Background: Cardiac disease is the most important medical cause of maternal mortality in South Africa. Management of women with cardiac disease in pregnancy is highly specialised and they should ideally be evaluated early in pregnancy and in a multidisciplinary fashion with the aim of formulating a perinatal management plan. In order to facilitate the effi cient management of these patients in the context of a large tertiary hospital in South Africa a combined obstetric-cardiac (O-C) clinic was established at Tygerberg Academic Hospital (TBH) in 2010. Objective: The purpose of this review is to describe the patient profi le of an obstetric-cardiac clinic in South Africa, specifi cally the TBH O-C clinic and to share the lessons learnt from establishing this clinic. Methods: Retrospective review performed at TBH, a referral centre in the Western Cape Province of South Africa. All women evaluated and/or managed at the Obstetric-Cardiac clinic between 10 August 2010 and 4 December 2012 were included. Results: There were 231 women, rheumatic heart disease (n=79; 34.2%) was the predominant cardiac disease followed by congenital heart disease (n=78; 33.8%), medical conditions (n=38; 16.4%) and previous peripartum cardiomyopathy (n=9; 3.9%). Eighty-two women (35.5%) were perceived to be extremely high risk and their entire pregnancies were managed in the Obstetric-Cardiac clinic. The most common RHD lesion was mitral regurgitation (34.2%) and mixed mitral valve disease (24.1%). The most frequent CHD was ventricular septal defects (n=27; 35%). Conclusions: The cardiac disease profi le of patients seen at this obstetric-cardiac clinic in a South African tertiary hospital refl ects a transition from the disease profi le of a typical developing country (high burden of rheumatic heart disease) to the disease profi le seen in a more developed country (high burden of congenital heart disease). This could indicate improved quality of socio-economic development and the health care system. The increasing complexity of cardiac pathology that has to be dealt with in pregnant patients presenting to a tertiary hospital requires close collaboration between the obstetrician, cardiologist, cardiac surgeon and anesthetist caring for these patients. A dedicated obstetric-cardiac clinic is a good model to utilise in a tertiary hospital when aiming to optimise the care of patients with cardiac disease in pregnancy.